Synthesis and Mechanical Characterization of Micro B4C Particulates Reinforced AA2124 alloy Composites - N, Fazil; V Venkataramana, V; Nagaral, Madeva; Auradi, V (International Journal of Engineering and Technology, 2018)
In the current era of aerospace, automobile and other various industries, light weighed aluminium metal matrix composites plays a very major role. Metal matrix composites are composed of base material as metallic which is reinforced with ceramic particulate as reinforcement material. This paper consists of the preparation of micro composites by two step stir casting process by the addition of B4C particulates (80-90Âµm) into the AA2124 matrix by varying different weight percentages of 3% and 6% at a temperature of 730-750ËšC. Further once the composites are prepared are subjected to characterization, the SEM revealed that there is good uniform distribution of micro particles in the aluminum by exhibiting a good bonding with matrix and EDS confirmed the presence of B and C elements. Different properties were evaluated like density, hardness, ultimate tensile strength and yield strength which revealed that there is an increase in the mechanical properties than compared to the base metal. Â Â Â